Monty Python’s Life of Brian - Burgon, Geoffrey Alan 1941-2010 (<<The>> Criterion Coll., 1999)
The Pythons satirize religion, capital punishment, revolutionary politics, terrorism, graffiti, science fiction, and a host of other topics through the story of Brian, a first-century Judean.
Bildformat 1.85:1 (enhanced for 16:9 widescreen). - New, restored high-definition digital transfer
Orig.: Großbritannien 1979
Enth. two exclusive audio commentaries: one by Terry Gilliam, Eric Idle and Terry Jones, the second by John Cleese and Michael Palin ; five rarely seen deleted scenes with audio commentary by the Pythons ; four original British radio ads ; documentary film "The pythons", shot on location during the making of "Life of Brian"
Keywords: Jesus Christus; Jesus Christ -- Caricatures and cartoons; Monty Python's life of Brian; Longs métrages - Grande-Bretagne; Politik; Religion -- Drama; Judaea, Wilderness of -- Politics and government -- Drama; Comedy films; Feature films; Religious films; Video recordings for the hearing impaired